«ΑΥΤΟ ΖΗΤΑΕΙ Ο ΛΑΟΣ, ΠΟΥ ΑΓΑΠΑΕΙ ΜΕ ΠΑΘΟΣ ΤΟ ΘΕΑΤΡΟ». ΟΙ ΚΡΙΤΙΚΕΣ ΘΕΑΤΡΟΥ ΤΟΥ ΓΙΩΡΓΟΥ ΣΕΒΑΣΤΙΚΟΓΛΟΥ ΣΤΟΝ ΡΙΖΟΣΠΑΣΤΗ (1945-1947) [«THAT IS WHAT THE PEOPLE WANT, WHO LOVE THEATRE WITH PASSION». THE THEATRE REVIEWS OF GIORGOS SEVASTIKOGLOU IN THE NEWSPAPER RIZOSPASTIS (1945-1947)] - Angelopoulos, Tasos (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The article presents and analyzes the reviews that the director, dramatist and translator, Giorgos Sevastikoglou (1913-1990) wrote in Rizospastis, the official newspaper of the Greek Communist Party, during the Greek Civil War (from 1945 to 1947). Through his reviews, not only he emerges as a connoisseur of the world theatre history and trends of his time, but he also develops a strong ideological vision for theatre and theatre criticism itself: theatre’s task is to guide and express the popular spectator. The critic, therefore, is the interpreter of the will of a specific kind of public and, based on this, Giorgos Sevastikoglou analyzes a wide range of performances, mainly arguing that form innovations on stage should also incorporate the appropriate, for this spectator, content.